Asymptotic Analysis of a Delayed SVIR Epidemic Model with Immigration - Djeffal, Khaled Boudjema; Mezouaghi, Abdelheq; Djilali, Salih; Zeb, Anwar (Journal of Applied Nonlinear Dynamics, 2026)
This research investigates an SVIR epidemic model with a time delay that represents the latency period and immigration into all classes. The presence of Immigration will eliminate the disease-free equilibrium, and then there is no extinction scenario of the epidemic, and we deduce that immigration will eliminate the notion of threshold dynamics, and hence there is no basic reproduction number. We obtained that the epidemic is always persistent and the unique endemic equilibrium is globally stable, which has been proved using the Lyapunov approach.